FEATURES OF MANAGEMENT OF INNOVATIVE PROCESS - A. Obukhova; E. Sitnikova (Вестник Северо-Кавказского федерального университета)
The innovation process consists of stages, actions, processes, activities, where all the innovative resources or innovative potential is aimed at achieving the main goal - the achievement of innovative development, the implementation of innovative activities by all subjects of the innovation system. Innovation process management involves a set of measures and activities aimed at forecasting, planning, analysis, organization, regulation, support, implementation, control, evaluation of the innovation process as a whole, where the entire innovation system operates in conjunction, interaction to achieve this goal. In general, the innovation process should be considered as a system in which all components interact with each other and act as a whole.